SMOKING AS A RISK FACTOR IN ATHLETES - Iva Miteva; Valentin Valchev; Todor Kundurzhiev (Journal of IMAB, 2023)
After the pandemic and at the beginning of 2023, our team carried out a survey among active athletes about the risks associated with smoking. The purpose of the study is to assess smoking as a risk factor in athletes using a survey method. Methods: The respondents were asked to participate anonymously in a survey consisting of 14 questions. We surveyed 50 active athletes (35 men and 15 women). Results: Forty-three of the participants were aged between 18 and 22 years old, and 7 were aged between 23 and 27 years old. Results: 30% of the surveyed athletes are smokers, 40% are non-smokers and 30% used to smoke in the past; 66% are familiar with the risk of smoking; 42% would support a ban on smoking in public; 22% report that cigarettes influence athletic achievements; 80% of the athletes consider that they are smoking due to stress; 34% think that only a health problem could make them quit smoking. Conclusions: The fact that 66% of the athletes are aware of the risks associated with smoking gives us hope in the combat against smoking. The effect of cigarettes on the human body should be emphasized. The survey showed that there are insufficient campaigns to raise awareness about the harmful effects of smoking which is key to quitting cigarettes.